Determinants of household food security and maternal dietary diversity in rural Gedeo zone, southern Ethiopia: Results from a cross-sectional study - Jisso, Meskerem; Biadgilign, Sibhatu; Tareke, Amare Abera; Tesfaye, Tizalegn; Zerfu, Tadesse Alemu (Frontiers Media, 2025)
Background: In Ethiopia, food insecurity and poor dietary diversity continue to affect maternal and child health, particularly in rural regions.